PERCEIVED BARRIERS OF CERVICAL CANCER SCREENING AMONG MARRIED WOMEN IN MINGGIR, GODEAN, GAMPING SUB-DISTRICTS, SLEMAN DISTRICT YOGYAKARTA - Yusi Riwayatul Afsah (Universitas Muhammadiyah Yogyakarta, 2017)
Abstract Coverage of cervical cancer screening in Indonesia has only reached 5% and cervical cancer in Indonesia is still relatively high. The aimed of this cross-sectional study were to explore perceived barriers of cervical cancer screening and regular screening history among 384 married women in Sleman, Yogyakarta. Data were collected using modified questionnaire items from Champion Health Beliefs Model Scale. Results showed that only 13.8% of respondent have regular screening. Most of respondent in both group Regular and Non-regular/Never had screening perceived that they preferred a female doctor to conduct a screening. Significant association was found between perceived barriers for screening and women’s regular screening history (p-value =0.000). Important barriers reported from this study were male physicians, time-consuming for screening procedure, and embarrassment. Effort to increase screening need to focus on women who have high perceived barriers so that cervical cancer screening’s promotion can be achieved.